Progress Toward Modeling and Optimization of Sustainable Machining Processes - KAYNAK, YUSUF (ASME, 2020)
The topic of sustainable machining has in recent times emerged as a significant and impactful area of research focus as it directly deals with environmental health and protection, economic growth and prosperity, and societal wellbeing with greater health and wellness. More specifically, sustainable machining at product, process, and system levels deals with reducing negative environmental impact, offering improved energy and resource efficiency, generating a minimum quantity of wastes, providing operational safety, and offering improved personal health. This paper summarizes recent efforts by the world research community in sustainable machining with a systematic approach for the analysis of machining processes that are broadly classified as sustainable, beginning with dry machining, and then near-dry (also known as minimum quantity lubrication (MQL)) and cryogenic machining processes. The paper also extends its analysis to a hybrid mode of sustainable machining that effectively combines cryogenic and MQL machining processes for improved productivity and machining performance. While a significant part of this paper presents experimental analysis, the progress being made in modeling and optimization has also been discussed in the paper. In particular, major challenges involved in model development for practical implementation, with a view to selecting optimum cutting conditions and cutting tool selection, are primarily discussed in the paper. The need for continued modeling efforts for achieving deployable optimized conditions for sustainable machining is highly recognized, and further research is required in numerous fronts integrating the various convergent disciplines such as materials, mechanics, computational sciences, economics, environmental sciences.
Keywords: cutting; machining; cryogenic machining; modeling; optimization; advanced materials and processing; sustainable manufacturing; sustainability; tribology tribology in manufacturing; MINIMUM QUANTITY LUBRICATION; MULTIPASS TURNING OPERATIONS; IMPROVED FUNCTIONAL PERFORMANCE; OPTIMUM CUTTING CONDITIONS; SLIP-LINE MODEL; AZ31B MG ALLOY; TOOL-WEAR; SURFACE INTEGRITY; INCONEL 718; METALWORKING FLUIDS